ANALISIS KEPUASAN WISATAWAN TERHADAP HUTAN PINUS LIMPAKUWUS KAWASAN WISATA BATURADEN KABUPATEN BANYUMAS - Diani Mustika Prianti; Priyanto Priyanto (Universitas Pakuan, 2022)
Limpakuwus Pine Forest is a new tourist attraction located in the Baturaden Tourist Area, about 40 km from Banyumas Regency. Furthermore, the strategic location of the Limpakuwus Pine Forest, which is at the foot of Mount Slamet, makes the Limpakuwus Pine Forest have beauty and natural beauty that is suitable as a tourist attraction for family, friends or couples. This study aims to analyze the influence of destination attributes and the quality of tourist services on tourist satisfaction in the Limpakuwus Pine Forest tourist attraction. This type of research is descriptive with a quantitative approach. The sample selection technique is carried out with certain considerations (purposive sampling) to tourists who have visited the Limpakuwus Pine Forest. The data collection process was carried out by distributing questionnaires to 78 respondents and literature sources that were in accordance with the research topic. Data analysis in this study used multiple linear regression. The results showed that the variable of destination attributes had a significant effect on the variable of tourist satisfaction. In addition, the variable quality of tourist services also has a significant effect on the variable of tourist satisfaction. For subsequent researchers, there is still much that can be researched related to the course of tourism activities in the Limpakuwus Pine Forest, such as tourist loyalty, promotional activities through social media and the application of sustainable tourism.